Answers

  • qais
  • Content Quality
2016-04-30T09:14:30+05:30
When the zeroes of the polynomial is α and β, the equation becomes
x²-(α+β)x +αβ =0
comparing this with the given equation,
k/(k-2) = 3
⇒k =3k -6
⇒2k =6
⇒k =3
1 5 1
The Brainliest Answer!
2016-04-30T09:14:57+05:30
We are given that the product of the zeros of the given quadratic  equation is 3

αβ = c/a

      = k/k-2 = 3 (given)

       = k = 3(k-2)
       = k  = 3k - 6
        = k - 3k = -6
       =  2k   = 6
        = k  = 3

2 5 2